Article RETRACTED due to manipulation by the authors Implementation of Archery Class Management at the Pre-Extracurricular Program Stage To Improve Archery Skills of Elementary School Students - Hendra Setyawan; Abdul Mahfudin Alim; A. Erlina Listyarini; Pamula Trisna Suri; Juni Mahsusi; Muhammad Imam Rahmatullah; Tatok Sugiarto; Abdul Aziz Purnomo Shidiq; Zhanneta Kozina; Özgür Eken; Francesca Latino; Francesco Tafuri; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Currently, archery is a sport that is growing in popularity in society. However, most elementary schools (ES) in Yogyakarta, Indonesia, do not yet organize archery extracurricular activities. This is due to the lack of human resources related to archery sports skills. Apart from that, it is also due to limited facilities and infrastructure. This research is quantitative with a one-group pretest-posttest pre-experimental design. The research was conducted at Muhammadiyah Jogokaryan ES with subjects aged 10-12 who participated in the pre-archery extracurricular program. The sample was taken using a simple random sampling method in classes IV-VI, totaling 15 students. The technique for collecting data on archery skills was carried out by giving archery tests at a distance of 5 meters in 12 sessions/rounds by shooting at 6 children. The results of the paired t-test sig value. 0.001 < 0.05 means there is a difference between the pre-test and post-test. The pre-test score was 59.53, and the post-test was 78.13, meaning there was a descriptive improvement. The n-gain effectiveness test result is 0.43, which is in the medium category. Findings from observations by researchers in the field also found that effectiveness was medium-level due to limited equipment and facilities for archery extracurricular activities. The conclusions are: (1) The implementation of archery class management at the pre-extracurricular program stage has a significant effect in improving ES students' archery skills; (2) The implementation of archery class management at the pre-extracurricular program stage in well-managed archery teaching has been proven to be effective in improving archery skills but only falls into the moderate effectiveness category, due to limited equipment and facilities for archery extracurricular activities; (3) Management of archery sports classes at the pre-extracurricular program stage requires planning, organizing, implementation/instruction and evaluation/assessment steps; (4) Support for equipment and facilities is needed for archery extracurricular activities at ES. This is to provide maximum archery skill achievement for ES students aged 10-12 years and as an encouragement for cultivating archery athletes in the city of Yogyakarta, Indonesia.